A Study on First-class Product Recovery Options of Closed-loop Supply Chain: Analysing Policy Instruments from The Triple Bottom Line for A Seamless Circular Economy Transition in EU Value Chain - Wijaya, Andy (2017)
As human ecology footprints are growing, such increasing population, fast expanding economic growth and high increasing price of materials, the need to shift from a linear consumption model to a cyclical model is urgently needed. The Circular Economy (CE), is considered as a potential approach where it upholds a closed-loop system where the economic value and technical properties of the material can be retained as long as possible. On the other hand, the First-class Recovery Options (FROs) in a Closed-loop Supply Chain (CLSC) is observed as a best practice in business operations that may principally function as sustainable manufacturing strategy, which has the capability of using product and input materials for more than one manufacturing cycle. However, CE is a holistic principle, which it still needs a set of policy interventions to create an increasing synchronous awareness between the society and the business actors. This dissertation focuses on the way to assess the existing policy instruments across EU members, in addressing root causes of the barriers to implementing FROs within CLSC from triple bottom lines viewpoint. The research method consisted of a wide review of relevant literature and the use of EU countries’ policy instruments to have the understanding why the unsolved problems exist in the real cases. This research produced a number key findings. The major one is, those root causes are indeed addressed unequally, as most EU countries focus on particular root causes, such market awareness, and process design. The main conclusion drawn from this research was each of those countries might not entirely solve all of those root causes by utilising their existing policy instruments. It is, therefore, to have a seamless transition, presenting information on successful initiatives, and showing a complete picture of policy instruments framework amongst members, are considered necessary. This research also argues on how to develop a set of policy instruments by taking the fundamental character of each root cause into consideration and combining it with business attributes of the FROs practices in a CLSC.